Genetic diseases: protection of interests of mother and child - Серова, О.А. (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
Modern medical technologies provide care for children with severe disabilities; however, medical and social support of children suffering from rare genetic diseases has many disadvantages. The change in legislation defining the conditions for obtaining the disability status limits the right of a child with a hereditary disease for assistance. The article deals with the questions of an integrated approach to the protection of the rights and legitimate interests of sick children as well as the development of regional centers for the diagnosis and treatment of rare diseases.
Keywords: hereditary; genetic; rare diseases; the rights of the disabled child; social support; наследственные; генетические; редкие заболевания; права ребенка-инвалида; социальная поддержка